Mapping of State Transportation Agencies' Practices and Perceptions in Project Bundling. Issue 7 (July 2022) - Shrestha, Saurav; Shan, Yongwei; Goodrum, Paul M.
State transportation agencies (STAs) have been using the project bundling method primarily on bridge projects. While many studies suggest that bundling bridges can reduce project costs and expedite project delivery, more research is needed to help STAs to achieve advanced use of project bundling by understanding the current state of the practice and perceptions about project bundling among STA representatives. This paper presents the detailed findings of a survey, including the perceived benefits, challenges, and risks involved in the bundling method among STA representatives. The survey found that project bundling helps reduce individual project costs in a bundle as well as agency administrative costs and provides an individual project with the flexibility to schedule around other projects in a bundle. Project bundling was found to have a major impact on the cost and delivery time of the project. The major factors that are considered for bundling effectiveness were found to be work type, project type, and spatial proximity. The major concern that most of the STAs had during bundling was that the bundled projects may eliminate the competition from smaller contractors. However, the concerns over the bundling method were found to be less among agencies with a high-level experience of bundling. The survey also found that the majority of STAs have not quantified the impact of the project bundling yet. The results from this study suggest that further research on bundling mixed-type projects and risks associated with bundled contracts is necessary.